Congenital and acquired defects in enamel of primary teeth: prevalence, severity and risk factors in Brazilian children - Almeida, L. K.Y. [UNESP]; Carvalho, T. S. [UNESP]; Bussaneli, D. G. [UNESP]; Jeremias, F. [UNESP] (Springer Nature, 2021)
Objective: This cross-sectional study evaluated the prevalence of tooth enamel defects and risk factors associated in primary dentition. Methods: A sample of 656 schoolchildren (population based), aged 4 years old, from Araraquara-SP (Brazil) was evaluated by two trained examiners according to the following indexes: Dental fluorosis (DF), deciduous molar hypomineralization (DMH), non-fluoride related developmental defects of enamel (DDE), tooth erosion and tooth attrition. Structured questionnaires identified socioeconomic condition, medical/dental history, behavior and dietary habits. Data were analyzed using Chi-square tests (p < 0.05). Results: Of the enamel congenital defects, DF was the most prevalent (6.1%, n = 40), followed by DMH (5.6%, n = 37). Of the acquired defects, attrition was the most prevalent (36.9%, n = 242), followed by erosion (2.4%, n = 16). The caries experience was similar between the affected children (29,5%; n = 94) and total sample (30.6%; n = 201). The etiological factors related to congenital defects were: not exclusively fed breast milk (p = 0.003) and jaundice at birth (p < 0.001); the association with acquired defects was found with vomiting frequent episodes (p = 0.037). Conclusion: The general prevalence of enamel defects in primary dentition in Araraquara was 48.6%. Enamel defects may be associated with health-related factors and current lifestyle.
Keywords: Enamel defects; Pediatric dentistry; Prevalence; Primary Tooth; Tooth enamel